Preparação e caracterização de nanocompósitos de Fe@SiO2, Fe@Fe3O4 e Fe3O4@PNIPAM - Nunes, Eloiza da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this work the obtainment of metallic iron nanoparticles in several non-aqueous (glycols) and in aqueous media through chemical reduction with sodium borohydride and the obtainment of core@shell structures Fe@SiO2 and Fe@Fe3O4, was investigated. The characterization results of poly(N-isoproprylacrylamide) (PNIPAM) based magnetic nanocomposites and bare polymeric nanogels (controls) synthesized through radical precipitation polymerization were also presented. The composition of the polymeric nanocomposites was varied as the type of co-monomer (acrylic acid and poly(ethyleneglycol) methylether methacrylate (PEGMA)), crosslinker (methylene bis-acrylamide (MBA) and poly(ethyleneglycol) diacrylate (PEGDA)) and precursor magnetic nanoparticle. The metallic nanoparticles and the core@shell Fe@SiO2 and Fe@Fe3O4 nanostructures were characterized by XRD, Mössbauer spectroscopy, XPS, SEM and TEM. The results show that the iron nanoparticles were composed of α-Fe and varying amounts of Fe1-xBx alloy and the size and morphology of the particles was dependent of the reaction media used. The strategies for metallic nanoparticles coating was efficient and chemically stabilized the magnetic cores. The Fe@SiO2 nanostructures was prepared by using alkoxysilanes precursors through the sol-gel process to produce the silica coating. The silica thickness could be controlled more efficiently in the case of bigger particles produced from chemical reduction in aqueous media. In the case of small nanoparticles the formation of aggregates was observed. The Fe@Fe3O4 core@shell structures were obtained by passivation of the metallic iron nanoparticles in a glycol solvent. The method of passivation enabled good oxidation control of the metallic surface to magnetite phase, avoiding the formation of non-magnetic oxy-hydroxides. The metallic to oxide phase ratio was determined by Rietveld refinement and was dependent of the type...

Neste trabalho foi investigada a obtenção de nanopartículas de ferro metálico em diferentes meios não aquosos (glicóis) e em água através da rota de redução com boroidreto e a obtenção de estruturas caroço@casca Fe@SiO2 e Fe@Fe3O4. Também são apresentados resultados da caracterização de nanocompósitos magnéticos à base poli(N-isopropilacrilamida) (PNIPAM) e de nanogéis poliméricos (controles) através do método de polimerização radicalar por precipitação. A composição dos nanocompósitos poliméricos foi variada quanto ao tipo de co-monômero (ácido acrílico e poli(etileno glicol) metiléter metacrilato (PEGMA)), reticulador (metileno bis-acrilamida (MBA) e poli(etileno glicol) diacrilato (PEGDA)) e nanopartícula magnética precursora. As nanopartículas metálicas e nanoestruturas Fe@SiO2 e Fe@Fe3O4 foram caracterizadas por DRX, espectroscopia Mössbauer, XPS, SEM e TEM. Os resultados obtidos demostraram que as nanopartículas de ferro metálico foram compostas de α-Fe e variáveis teores de liga de Fe1-xBx e a morfologia e tamanho de partícula variaram em função dos diferentes meios reacionais empregados. As metodologias de recobrimento das partículas metálicas precursoras foram eficazes na estabilização química do caroço magnético. O recobrimento com sílica para obtenção das estruturas Fe@SiO2 foi realizado empregando-se precursores alcoxissilanos através do processo sol-gel. A espessura da camada de sílica pode ser controlada mais eficientemente no caso de partículas maiores oriundas de redução no meio aquoso e no caso de nanopartículas pequenas observou-se a formação de agregados. As estruturas Fe@Fe3O4 foram obtidas pela passivação das nanopartículas metálicas em solvente glicol. A metodologia de passivação demostrou a possiblidade de oxidação controlada da superfície para fase de magnetita evitando a formação de óxi-hidróxidos não...
Keywords: Nanoestruturas; Magnetita; Silica; Nanogéis; Nanopartículas; Nanoparticles